2019
DOI: 10.1152/jn.00141.2019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of levodopa on electroencephalographic biomarkers of the parkinsonian state

Abstract: The objective of this study was to evaluate proposed electroencephalographic (EEG) biomarkers of Parkinson’s disease (PD) and test their correlation with motor impairment in a new, well-characterized cohort of PD patients and controls. Sixty-four-channel EEG was recorded from 14 patients with rigid-akinetic PD with minimal tremor and from 14 age-matched healthy controls at rest and during voluntary movement. Patients were tested off and on medication during a single session. Recordings were analyzed for phase-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
67
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(72 citation statements)
references
References 44 publications
(70 reference statements)
4
67
1
Order By: Relevance
“…The proportion of participants with DLB taking psychoactive drugs was greater compared to participants with AD in all studies where this information was disclosed. Psychoactive drugs such as benzodiazepines, antipsychotics, antidepressants, anticonvulsants, and dopaminergic agents are commonly prescribed and result in some EEG changes such as enhanced beta activities, increase in theta or delta power, and triphasic waves [88,89]. Secondly, most studies did not comment on whether the EEG assessors were blinded to the clinical diagnosis which constitutes a potential bias although this may be less of a factor in quantitative studies compared to qualitative studies which are dependent on a subjective rating.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of participants with DLB taking psychoactive drugs was greater compared to participants with AD in all studies where this information was disclosed. Psychoactive drugs such as benzodiazepines, antipsychotics, antidepressants, anticonvulsants, and dopaminergic agents are commonly prescribed and result in some EEG changes such as enhanced beta activities, increase in theta or delta power, and triphasic waves [88,89]. Secondly, most studies did not comment on whether the EEG assessors were blinded to the clinical diagnosis which constitutes a potential bias although this may be less of a factor in quantitative studies compared to qualitative studies which are dependent on a subjective rating.…”
Section: Discussionmentioning
confidence: 99%
“…Abundant Beta bursts have also been reported in the basal ganglia of PD patients, this Beta pattern being reversible with L-DOPA [26]. Other EEG biomarkers of PD can also be modified with L-DOPA treatment [27]. In our study, we observed a marked improvement in EEG activity (decrease in Theta-Delta and increase in Alpha activity), in parallel with a clinically relevant amelioration of psychomotor function, especially in PD-NC and PD-MCI, and to a lesser extent in PD-DEM (▶ Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Our findings provide support for cortical phase-amplitude coupling as a marker of pathological synchronization in Parkinson's disease that responds to deep brain stimulation therapy, and is correlated with symptomatic improvement. In a prior study, levodopa induced PAC reduction was more closely related to bradykinesia than rigidity [6], which may reflect differences in severity of specific motor signs between the two groups. We also provide evidence for the first time that DBS-induced changes in cortical synchronization in Parkinson's disease may be detected using scalp EEG, offering implications for the use of noninvasive recording techniques in the development of control signals for closed-loop DBS paradigms.…”
mentioning
confidence: 82%